Gamification for enhancing Web 2.0 based educational activities: The case of pre-service grade school teachers using educational Wiki pages - ÖZDENER DÖNMEZ, NESRİN (ELSEVIER SCIENCE BV, 2018)
This study seeks to uncover the effects of using gamification elements in courses that make use of a Wiki environment on the participation rates of undergraduate students in Wiki-based course activities as well as on student academic success in the course. Owing to the fact that the group of students chosen for the study consisted of pre-service grade school teachers, their opinions on the use of the Wiki environment along with its embedded gamification elements in their future careers have been sought. Of particular interest were the considerations of pre-service teachers concerning the age levels of a target audience that they believed would benefit from instruction with this particular educational tool. Following a mixed-research methodological pattern, the study was conducted in two consecutive stages. The first stage involved a quasi-experiment and the second was handled as a case study. In order to examine the long-term effects of Wild activities supported by gamification elements on student academic success, a repeated measures analysis of variance (ANOVA) statistical test was conducted based on scores from an initial pre-knowledge test, an applied interim examination, and a final examination. In order to determine the opinions of teacher candidates regarding Wild activities and the process of gamification, results from an open-ended questionnaire were consulted. It was eventually discovered that students in both the Wild-only (p = 0.02) and gamified-Wiki (p = 0.00) activity groups displayed significantly greater academic success compared to a control group. Although gamification elements also caused a significant difference between the two Wiki groups in terms of the number of times content is displayed (1670 > 637) and edited (38 > 18), it was observed that participation rates fell over time in both groups. As for academic success, there was no difference between the two Wiki groups (p = 0.92). It was found that teacher candidates regard Wiki and gamification activities positively. Also, it was noted that they did not possess an adequate level of consciousness of the fact that student capabilities are an important factor in making effective use of technology. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Wild; Gamification; Web 2.0; Integration of technology in education; COMPETITION; KNOWLEDGE; PERCEPTIONS; TECHNOLOGY; IMPACT